The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3gc00205e
|View full text |Cite
|
Sign up to set email alerts
|

High-purity polypropylene from disposable face masks via solvent-targeted recovery and precipitation

Abstract: The high use of disposable face masks since the start of COVID-19 has globally generated 4.68-6.24 million tons per year of waste from personal protective equipment. Disposable face masks are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Other studies have also concluded that the solvent based dissolution–precipitation process can be economically feasible at a capacity higher than 5000–6000 MT per year. 23,24…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also concluded that the solvent based dissolution–precipitation process can be economically feasible at a capacity higher than 5000–6000 MT per year. 23,24…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the STRAP process had lower environmental impacts than virgin polymer films 22,23 and could be economically feasible at a processing capacity higher than 6000 MT per year. 23 Yu et al 24 conducted TEA and LCA of the STRAP process for polypropylene based (PP) disposable face masks with polymer recovery via a cooling approach. The majority of the above-mentioned studies on STRAP processes looked at multi-layer films containing PET along with other resins such as polyethylene (PE), ethylene vinyl alcohol (EVOH), and ethylene vinyl acetate (EVA).…”
Section: Introductionmentioning
confidence: 99%
“…S1†) operating at a moderate temperature, minimizing the risks associated with more hazardous solvents and optimizing the efficiency of PP recovery. The investigation involves studying the dissolution kinetics of PP in the novel solvent and comparing it with existing dissolution models following a dissolution–precipitation technique 9,10 (see the ESI†). The dissolution behaviour of virgin PP and PP-rich carpet waste fibres (Fig.…”
mentioning
confidence: 99%